THE IMPACT OF PT BIO FARMA CORPORATE REPUTATION, PRODUCT QUALITY ON INSTITUTIONAL CUSTOMER LOYALTY - Terisa, Ellen; WS, Paidi; Samry, LM (Journal of Management and Leadership, 2024)
Abstract The pandemic of COVID-19 disrupted supply chain systems, with long-term consequences. This study examines the impact of Covid-19 disruption, resilience, and adaptation strategies on the company's supply chain performance (SCP). The research is a case study conducted sequentially with a qualitative and quantitative approach at PT XX, a pharmaceutical company in Indonesia, under interviews and document analysis. The techniques and analytical tools used in this study are multiple linear regression using Minitab, which included t-test, F regression, R-square analysis, and moderation regression analysis to measure the relationship between variables. The study's findings indicate that the Covid-19 disruption has had a negative impact on SCP. However, the SCR, SCRM, SCI, and SCE are all components of resilience that positively influence SCP. This research also shows that adaptation strategies such as intertwining, substitution, and repurposing improve the SCP. As a result, to achieve long-term supply chain performance and sustainability, companies should focus on integrating business operations, resilience, and adaptation strategies to deal with the consequences of major disruptions. Improvements in several resilience parameters and the implementation of several adaptation strategies are required to accelerate recovery and enhance supply chain performance. Keyword: disruption, resilience, adaptation strategy, and supply chain performance (SCP)